2012
DOI: 10.1098/rstb.2011.0418
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from community-based payment for ecosystem service schemes: from forests to rangelands

Abstract: Climate finance investments and international policy are driving new community-based projects incorporating payments for ecosystem services (PES) to simultaneously store carbon and generate livelihood benefits. Most community-based PES (CB-PES) research focuses on forest areas. Rangelands, which store globally significant quantities of carbon and support many of the world's poor, have seen little CB-PES research attention, despite benefitting from several decades of community-based natural resource management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 93 publications
(97 reference statements)
0
41
0
1
Order By: Relevance
“…We believe that the topics treated here are in urgent need of conceptual advances in order to improve the livelihood of people living in drylands (e.g. desertification and management of natural resources to improve human well-being in developing areas [133,163]). We expect that the multidisciplinary, multi-organismal approach followed in this theme issue will advance our understanding of the projected effects of global change in drylands, and will stimulate further research on this important topic.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the topics treated here are in urgent need of conceptual advances in order to improve the livelihood of people living in drylands (e.g. desertification and management of natural resources to improve human well-being in developing areas [133,163]). We expect that the multidisciplinary, multi-organismal approach followed in this theme issue will advance our understanding of the projected effects of global change in drylands, and will stimulate further research on this important topic.…”
Section: Discussionmentioning
confidence: 99%
“…The simplicity of our modelling approach, whenever long-term demographic data is available, together with the robustness of the climatic projections, calls for its application to other species, particularly when considering the urgent need to understand responses to climate change of more desert species that might prove important in alleviating poverty. If our findings are applicable to other desert plant species, the implications for carbon storage [103,104], particularly below-ground, exploitation of natural resources [105], and self-sustainability should be re-evaluated in the context of the large amount of dryland human inhabitants [2], a number that is only expected to increase owing to desertification [3]. (a) Future directions Clearly, we are still far from achieving a detailed understanding of how climate change will affect desert plant species in general, or whether it will at all, given their potential for buffering abiotic stochasticity.…”
Section: Climate Change Precipitation and Desert Plant Demographymentioning
confidence: 99%
“…The results showed that the framework is a more efficient alternative and complement to traditional regulatory approaches for handling the externality of environment protection. PES is also an effective method to balance the relationship between suppliers and beneficiaries [53][54][55]. By developing a formal, regional PES framework for cropland protection, we established an efficient method to protect cropland and to improve ecosystem services.…”
Section: Discussionmentioning
confidence: 99%